Strain-based room-temperature non-volatile MoTe2 ferroelectric phase change transistor - Hou, Wenhui; Azizimanesh, Ahmad; Sewaket, Arfan; Peña, Tara; Watson, Carla; Liu, Ming; Askari, Hesam; Wu, Stephen M. (Nature nanotechnology, 2019)
The primary mechanism of operation of almost all transistors today relies on the electric-field effect in a semiconducting channel to tune its conductivity from the conducting ‘on’ state to a non-conducting ‘off’ state. As transistors continue to scale down to increase computational performance, physical limitations from nanoscale field-effect operation begin to cause undesirable current leakage, which is detrimental to the continued advancement of computing 1 , 2 . Using a fundamentally different mechanism of operation, we show that through nanoscale strain engineering with thin films and ferroelectrics the transition metal dichalcogenide MoTe 2 can be reversibly switched with electric-field-induced strain between the 1T′-MoTe 2 (semimetallic) phase to a semiconducting MoTe 2 phase in a field-effect transistor geometry. This alternative mechanism for transistor switching sidesteps all the static and dynamic power consumption problems in conventional field-effect transistors 3 , 4 . Using strain, we achieve large non-volatile changes in channel conductivity ( G on / G off ≈ 10 7 versus G on / G off ≈ 0.04 in the control device) at room temperature. Ferroelectric devices offer the potential to reach sub-nanosecond non-volatile strain switching at the attojoule/bit level 5 – 7 , with immediate applications in ultrafast low-power non-volatile logic and memory 8 while also transforming the landscape of computational architectures because conventional power, speed and volatility considerations for microelectronics may no longer exist. Strain-induced phase change in MoTe 2 enables reversible channel conductivity switching in a field-effect transistor geometry.